An evaluation on Malaysian Standards Online (MS Online) / Harleena Mohd Azhar (Faculty of Business Management, 2006)
MS Online is a new way for SIRIM Berhad in selling Malaysian Standards to their target customer. Since it being introduced to the public, the researcher wants to see the overall performance of it. Therefore, the objective of this study is (l) To analyze the difference (gap) of an important attribute of MS Online (Speedy Access, Cost Saving, Easy Search, Online Secured Payment). (2) To measure the customer satisfaction on MS Online's attlibutes. The attributes of MS Online is the focus of the study which are Speedy Access, Cost Saving, Easy Search and Online Secured Payment. Understanding the customer expectation and satisfaction level towards those attribute and whether they are satisfied or dissatisfied with the attributes provided by company is important as it reflects the performance of MS Online. This paper consists of five chapters which explain the stages in completing the study. Chapter 1 explains the introduction and background of the study. Chapter 2 explains the literature review, which relates to the subject studied and theoretical framework which provide to guide to the research process. In chapter 3, research methodology which consist of methods and sampling techniques be used. Data findings and discussions is explained in chapter 4, chapter 5 contain summary of results and findings, which explain conclusions and recommendations.